Synthesis and Characterization of Silica-Potassium-Phosphate Solid Fertilizer Derived from Sugarcane Bagasse Ash - Naufal Ramadhan Ahmad; Febryan Rama Syahputra; Ika Nawang Puspitawat; Sani Sani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This research aimed to synthesise and characterise Silica-Potassium-Phosphate (Si-K-P) solid fertiliser using sugarcane bagasse ash as a silica source. The process involved silica extraction using potassium hydroxide (KOH) followed by polymerization with Phosphoric Acid () under varying conditions of pH (5, 6, 7, 8, 9) and alkali silica concentrations (16.67%, 20%, 25%, 33.3%, and 50%). Characterisation methods included X-ray fluorescence (XRF), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The results revealed that the raw sugarcane bagasse ash contained 69.2% silica (). The synthesis conditions significantly influenced the final nutrient composition; the highest silica content of 22.8% was achieved at pH 7, the maximum potassium content of 59.9% at pH 9, and the highest phosphate content of 37.7% at pH 5. FTIR analysis confirmed the formation of siloxane (), while SEM imaging showed a porous agglomerated morphology. This study demonstrates that sugarcane bagasse ash can be effectively converted into a value-added multinutrient fertilizer. Contribution to Sustainable Development Goals (SDGs): SDG 2: Zero HungerSDG 12: Responsible Consumption and ProductionSDG 9: Industry, Innovation and InfrastructureSDG 13: Climate Action